Study of Representative Volume Elements in Terms of Morphology - Dodla S. (My University, 2025)
Inconel alloys are used in aerospace applications thanks to their excellent mechanical properties and better corrosion resistance. The Inconel polycrystal is used as the starting material for the investigation. Voronoi tessellations model has been developed for the polycrystal using the UMAT subroutine. The material parameters are identified using an elasto-viscoplastic model with the help of the Levenberg–Marquardt algorithm (Bertram in Elasticity and plasticity of large deformations—an introduction, 3rd edn. Springer, Berlin, 2012 [1]; Dodla et al. in Comput Mater Sci 101:29–38, 2015 [2]). Generally, the mechanical behavior of microstructured material can be predicted using the representative volume element (RVE) technique. The cubical RVEs with periodic boundary conditions and periodic microstructure are quite popular since they can achieve better convergence than non-periodic cases. The current work discusses spherical and cylindrical RVEs since they have advantages compared to cubical RVEs. In particular, the convergence of three RVEs is discussed using periodic boundary conditions. From the numerical results, it is clear that the spherical RVEs are more advantageous, and there is a reduction in the computational time. The numerical results regarding deformation behavior have been compared with the experiments. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.